Analysis of Translation Techniques of Grand Sheikh Al-Azhar's Speeches on Sanad Media's YouTube Channel - Sandriwan, Andri; Syihabuddin, Syihabuddin; Supriadi, Rinaldi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
AbstractIn the digital age, YouTube serves as a major resource for learning Arabic. Language and cultural variances necessitate the need for translation to comprehend the messages conveyed in the videos. The purpose of this study is to analyze translation techniques in the speech of the Grand Sheikh of Al-Azhar on the YouTube channel of Sanad Media Account, specifically focusing on the translated text entitled